Chinese research perspectives on educational development. - Dongping, Yang (Chinese research perspectives on education ;, 2014)
In this volume, readers are brought up to date on the main educational issues and events of 2012. 2012, witnessed the deepening of education reform in terms of promoting education equity and improving rural education and balanced development of compulsory education.